Intrinsic risk factors of non-contact ankle sprains in soccer - A prospective study on 100 professional players - K Fousekis; E. Tsepis; G. Vagenas (American Journal of Sports Medicine, 2012)
Background: Ankle sprain is an extremely common injury in soccer players. Despite extensive research, the intrinsic cause of this injury under noncontact conditions remains unclear. Purpose: To identify intrinsic risk factors for noncontact ankle sprains in professional soccer players. Study Design: Cohort study; Level of evidence, 2. Methods: One hundred professional soccer players were assessed in the preseason for potential risk factors of noncontact ankle. sprains. The assessment included (A) ankle joint asymmetries (right-left) in isokinetic muscle strength, flexibility, proprioception. and stability; (B) somatometric asymmetries; (C) previous injuries; and (D) lateral dominance traits. Noncontact ankle sprains were prospectively recorded and diagnosed for a full competition period (10 months). Results: Seventeen of the players sustained at least 1 noncontact ankle sprain. Logistic regression revealed that players with (A) eccentric isokinetic ankle flexion strength asymmetries (odds ratio [OR] = 8.88; 95% confidence interval [CI], 1.95-40.36, P = .005), (B) increased body mass index (OR = 8.16; 95% CI, 1.42-46.63, P = .018), and (C) increased body weight (OR = 5.72; 95% CI, 1.37-23.95, P = .017 ) each had a significantly higher risk of a noncontact ankle sprain. A trend for younger players (OR = 0.28; 95% CI, 0.061-1.24, P = .092) and for players with ankle laxity asymmetries (OR = 3.38; 95% CI, 0.82-14.00, P = .093) to be at greater risk for ankle sprain was also apparent to the limit of statistical significance (.05<P<.10). Conclusion: Functional strength asymmetries of the ankle flexors and increased body mass index and body weight raise the propensity for ankle sprains in professional soccer players. Age and asymmetries in ankle laxity are potential factors worth revisiting, as there was an indication for younger players and players with ankle instability to be at higher risk for ankle injury. Proper preseason evaluation may improve prevention strategies for this type of injury in soccer.